Meningkatkan Kemampuan Membaca dan Menulis dengan Cardletters Siswa Kelas 2 SDN Madyocondro - Lestiarini Isnani; Kun Hisnan Hajron (Prosiding Konferensi Ilmiah Dasar, 2022)
This study aims to improve the ability of Madyocondro Elementary School students in reading and writing because students have low reading and writing skills. This research was conducted at SDN Madyocondro Magelang which was attended by 10 grade II students. In improving reading and writing skills, the CAR research method uses cardletters as learning media. In the results of the analysis of the first cycle table data before the action, the average grade II students at Madyocondro Elementary School at the beginning of the assessment were still low, namely 56.6 for reading and 53 for writing. While in the second cycle after the action for the average value of the reading class is 70.4 and writing is 70.25 with the number of students completing 7 out of 10 students. So it can be concluded that the increase in student scores is 13.8% in reading and 17.25% in writing.